2004
DOI: 10.1007/s11664-004-0061-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth of large-diameter ZnTe single crystals by liquid-encapsulated melt growth methods

Abstract: The 80-mm-diameter ZnTe single crystals were successfully obtained by the liquid-encapsulated Kyropoulos (LEK) method. Both Ͻ100Ͼ-and Ͻ110Ͼ-oriented single crystals were reproducibly grown by using ZnTe seed crystals. Furthermore, 80-mm-diameter, Ͻ100Ͼ and Ͻ110Ͼ ZnTe single crystals were obtained by the pulling method. The etch pit densities (EPDs) of the grown crystals by the LEK and pulling methods were lower than 10,000 cm Ϫ2 . The strain in the grown crystals by the pulling method was lower than that of LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Nakagawa et al [37] showed that their etchants were effective at B-face of CdTe, but Fewster [38] claimed that these etchants were actually effective at the A-face of CdTe which was also confirmed with XRD studies [39]. Some studies, used Nakagawa solutions with different ratio of HF:H 2 O 2 :H 2 O to calculate the etch pit density (EPD) on the ZnTe films [40].…”
Section: Resultsmentioning
confidence: 95%
“…Nakagawa et al [37] showed that their etchants were effective at B-face of CdTe, but Fewster [38] claimed that these etchants were actually effective at the A-face of CdTe which was also confirmed with XRD studies [39]. Some studies, used Nakagawa solutions with different ratio of HF:H 2 O 2 :H 2 O to calculate the etch pit density (EPD) on the ZnTe films [40].…”
Section: Resultsmentioning
confidence: 95%
“…However, the growth is conducted with following differences from the CZ method [ 91 ] : 1) complete crystallization of the melt in the crucible is carried out; 2) the final shape of the crystal is defined by the shape of the crucible; 3) the seed is water cooled; 4) rotation of the seed takes part only at the beginning of the growth; 5) a slow pulling of the seed up is performed only at the initial part of the growth followed by controlled cooling of the system; and 6) pulling is stopped when the crystal reaches bottom of the crucible. In this way, the single crystals of various sizes (small to large) of semiconductors, for example, ZnTe, [ 92 ] sapphire, [ 93 ] including halides such as CsBr (9 inch diam. ), [ 94 ] KX:Cu (X ═ Cl, Br, I), [ 95 ] or LiF, [ 96 ] were prepared.…”
Section: Bulk Crystal Growth Of Halide Materialsmentioning
confidence: 99%
“…[8,9] In order to obtain ZnTe crystal from the standard Zn: Te = 1:1 mole ratio solution, various techniques have been developed in the past, such as vertical gradient freezing method, vertical Bridgman method, liquid encapsulated kyropoulos method, liquid-encapsulated vertical gradient freezing method, and so on. [10][11][12][13][14] Nevertheless, the ZnTe crystals prepared via these techniques are usually deviate from stoichiometric ratio and the reproduction of large size crystal is poor. In recent years, an interesting Te flux method was explored which has several outstanding advantages compared to the above methods: i) the crystal growth temperature can be sharply reduced; ii) ZnTe crystal with standard 1:1 composition can be achieved; iii) the apparatus for crystal growth is much simple and inexpensive.…”
Section: Introductionmentioning
confidence: 99%